Harmony of Religions. Vedanta Siddhanta Samarasam of Tayumanava - B. V. Venkatakrishna (Journal of Dharma, 1994)
Fr. (Dr.) Thomas Manninezhath’s book Harmony of Religions is a fine, erudite contribution in the context of the on-going interreligious. dialogue in India and abroad. The title of the book may appear too wide or ambitious for the author does not deal with the religjons, as the sub-title of the book clarifies.